Identifying different transcribed proteins in the newly described Theraphosidae Pamphobeteus verdolaga - Estrada-Gomez, Sebastian; Johana Vargas-Munoz, Leidy; Saldarriaga-Cordoba, Monica; Cifuentes, Yeimy [UNESP]; Perafan, Carlos (Elsevier B.V., 2017)
Theraphosidae spider venoms are well known for possess a complex mixture of protein and non -protein compounds in their venom. The objective of this study was to report and identify different proteins translated from the venom gland DNA information of the recently described Theraphosidae spider Pamphobeteus verdolaga. Using a venom gland transcriptomic analysis, we reported a set of the first complete sequences of seven different proteins of the recenity described Theraphosidae spider P. verdolaga. Protein analysis indicates the presence of different proteins on the venom composition of this new spider, some of them uncommon in the Theraphosidae family. MS/MS analysis of P. verdolaga showed different fragments matching sphingomyelinases (sicaritoxin), barytoxins, hexatoxins, latroinsectotoxins, and linear (zadotoxins) peptides. Only four of the MS/MS fragments showed 100% sequence similarity with one of the transcribed proteins. Transcriptomic analysis showed the presence of different groups of proteins like phospholipases, hyaluronidases, inhibitory cysteine knots (ICK) peptides among others. The three database of protein domains used in this study (Pfam, SMART and CDD) showed congruency in the search of unique conserved protein domain for only four of the translated proteins. Those proteins matched with EF-hand proteins, cysteine rich secretory proteins, jingzhaotoxins, theraphotoxins and hexatoxins, from different Mygalomorphae spiders belonging to the families Theraphosidae, Barychelidae and Hexathelidae. None of the analyzed sequences showed a complete 100% similarity. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Pamphobeteus verdolaga; Theraphosidae; Transcriptomic; Proteomic